Pengaruh Konten Akun Instagram @Sisilism2.0 Terhadap Kesadaran Kekerasan Seksual di Kalangan Remaja - Nindy Yekti Chotimah; Bambang Sujarwadi (Jurnal Ilmiah Manajemen Informasi dan Komunikasi, 2023)
Sexual violence is often a problem that affects teenagers, therefore sex education for teenagers is very important. Technological developments encourage the emergence of new media to meet human needs for communication and information. Instagram is a social media in the form of a smartphone application for disseminating information. The @sisilism2.0 account is an account that uploads information about sex education. The aim of this research is to find out whether the content of the Instagram account @sisilism2.0 influences awareness of sexual violence among teenagers. This research uses a quantitative approach with data collection techniques using an online questionnaire. The population in this study is followers of the @sisilism2.0 account. The sample was taken using a random sampling technique. Respondents are male or female aged 15-25 years old, followers of the @sisilism2.0 account, actively using Instagram and interact with the @sisilism2.0 account, also understand the content of the @sisilism2.0 Instagram account. The number of sample members was 96 people. The data analysis method in this research used the classic assumption test, simple regression analysis, and coefficient of determination. Data processing used the SPSS version 25 program. The research results obtained show that the content of the Instagram account @sisilism2.0 has a significant influence on self-awareness of teenagers regarding sexual violence by 64%, while the remaining 36% is influenced by other variables outside the research.